Urban Spatial Assessment of Edirne in the 15th Century According to Pietro Del Massaio's Plan - Ozkok, Mete Korhan; Yenen, Zekiye (TURK TARIH KURUMU, 2023)
Edirne was one of the capital cities of the Ottoman Empire, but even so, written and visual resources on the spatial development process are limited, especially for the period prior to the 19(th) century. The fact that the oldest known maps of Edirne belong to after 1854 is an issue that creates limitations in historical, spatial investigations. As a result of researches, a plan for Edirne/Kaleici was determined in the copy of Ptolemy's Geography named Latin 4802 prepared in the 15(th) century. Due to the changes observed in cartography and copy production between the 15(th)-16(th) centuries, the determined plan is the only example representing that period. The aim of this article is to make inferences about the spatial structure of Edirne/Kaleici Region in the 15(th) century, based on this plan. Within the scope of the study, the plan was examined through three main topics: the city walls and gates, road lines and urban functions. Additional resources, such as historical records, plans and maps, were used in the evaluation process. The original academic contribution of the study is to pave the way for further discussions on the spatial development and urban history for Edirne with this plan discussed for the first time in the literature. In addition, it has been determined based on the plan that the Kaleici region has the characteristics of a service region, especially in terms of religious/public facilities.
Keywords: Edirne; Urban History; City Plans; Ptolemy; Geography; Pietro del Massaio; VENICE; MAPS; Archaeology; History